Solar System Battery Backups for Reactor Coolant Pumps During Electricity Outages Resulting from Natural Disasters - Md. Shamsul Huda Sohel (International Journal of Nuclear Security, 2017)
In a nuclear power plant, its coolant system is major safety equipment. Coolant system failure causes several accidents in nuclear history. There are so many causes for coolant system failure. One of them is lack of electric power for coolant pumps. In typically NPP there is backup system for power redundancy. In this article, focus on reactor coolant system and its backup power when main grid lines failure. Here discuss about solar backup power for batteries and increases a safety lines for reactor coolant pumps. So, our main goal is providing a battery backup from reliable natural source and ensuring electricity for coolant pumps.
Keywords: PV solar cell; KWh; Coolant Pump; MW; LOCA; Coolant System; Grid system; Wp; Diesel Generator; Deep cycle battery; Inverter; NPP